Outcome of extracorporeal membrane oxygenation use in severe accidental hypothermia with cardiac arrest and circulatory instability: A multicentre, prospective, observational study in Japan (ICE-CRASH study). (January 2023) - Takauji, Shuhei; Hayakawa, Mineji; Yamada, Daisuke; Tian, Tian; Minowa, Keita; Inoue, Akihiko; Fujimoto, Yoshihiro; Isokawa, Shutaro; Miura, Naoya; Endo, Tomoyuki; Irie, Jin; Otomo, Gen; et al.
Abstract: Aim: To elucidate the effectiveness of extracorporeal membrane oxygenation (ECMO) in accidental hypothermia (AH) patients with and without cardiac arrest (CA), including details of complications. Methods: This study was a multicentre, prospective, observational study of AH in Japan. All adult (aged ≥18 years) AH patients with body temperature ≤32 °C who presented to the emergency department between December 2019 and March 2022 were included. Among the patients, those with CA or circulatory instability, defined as severe AH, were selected and divided into the ECMO and non-ECMO groups. We compared 28-day survival and favourable neurological outcomes at discharge between the ECMO and non-ECMO groups by adjusting for the patients' background characteristics using multivariable logistic regression analysis. Results: Among the 499 patients in this study, 242 patients with severe AH were included in the analysis: 41 in the ECMO group and 201 in the non-ECMO group. Multivariable analysis showed that the ECMO group was significantly associated with better 28-day survival and favourable neurological outcomes at discharge in patients with CA compared to the non-ECMO group (odds ratio [OR] 0.17, 95% confidence interval [CI]: 0.05–0.58, and OR 0.22, 95%CI: 0.06–0.81). However, in patients without CA, ECMO not only did not improve 28-day survival and neurological outcomes, but also decreased the number of event-free days (ICU-, ventilator-, and catecholamine administration-free days) and increased the frequency of bleeding complications. Conclusions: ECMO improved survival and neurological outcomes in AH patients with CA, but not in AH patients without CA.